Analysis Of The Influence Of Loan To Deposit Ratio, Capital Adequacy Ratio, Non-Performing Loan, Operational Efficiency Ratio, And Total Asset Turnover On Return On Asset Of Commercial Bank Listed On The Indonesian Stock Exchange Period 2019-2023 - Situmorang, Duma Rahel; Sagala, Farida; Silitonga, Ivo Maelina; Panjaitan, Rike Yolanda; Sagala, Lamria (Program Studi Akuntansi Universitas Simalungun, 2024)
The aim of this study to determine the effect of the loan to deposit ratio, capital adequacy ratio, non perfoming loan, operational efficiency ratio, total asset turnover on thw return on assets of commercial banks on the BEI for the 2019-2023 period. This research is a type of causal associative research with the research population being conventional commercial banks registered with the BEI in 2019-2023 which amounted to 45 banks. The sample is done by purposive sampling in order to obtain 28 banks that match the criteria and become the research sample. The type pf data used is secondary data with data collection using the method of documentation and literature study. The data analysis technique used is a multiple regression analysis. The results showed that partially operational efficiency ratio had a positive and significant effect on return on assets. Meanwhile, loan to deposit ratio and non performing loan have a positive and do not have a significant effect on return on assets. Capital adequacy ratio and the total asset turnover had a negative and do not significant effect on return on assets. Simultaneously, all independent variables affect the return on assets of conventional commercial banks registered with the BEI